A utilização da tecnologia assistiva como um recurso para inclusão escolar de alunos com sequelas de mielomeningocele - Assis, Caroline Penteado de (2010)
Research on the inclusion of students with myelomeningocele held in the country discuss only the access of students to the school context. Further research in this area of education has become necessary to investigate directly the reality of these students in the regular schools. As these students can develop various sequelae that interfere with school performance there is a need for the use of assistive technology to provide greater autonomy and independence in the school context. Therefore, the aim of this study was to identify, analyze and discuss the use of Assistive Technology, according to the consequences presented by the students with myelomeningocele included in regular schools. There were eleven participants, including four children with sequelae of myelomeningocele and seven teachers (four in the regular classroom and three from the specialized educational services). For data collection five instruments were used, built specifically for this study: two interview scripts, which described the inclusion of pupils, in the opinion of the teachers of regular classrooms and a Resource Scale of Teachers' Perception on Myelomeningocele which aimed to survey the academic performance of pupils and the level of aid of the technologies used by them in the school environment, the Script Observation of Student Performance with myelomeningocele used to describe the student achievement in the school context and finally Script Categorization of the Use of Assistive Technology in the School Context, which provided the guidance note on the use of technology in the school context. The results indicated that demand exists due to deployment of resources on school performance presented by students with myelomeningocele sequelae, but the unique features found to promote the participation of four students in the school context are two wheelchairs and an orthesis for positioning the ankle, ie, resources that the student brought to school. It was possible to see that there is little or no knowledge on the part of school personnel about the potential for practical implementation of technology resources, which are related to lack of training and identifying the real needs and potential of students.